Pengaruh Kompetensi dan Motivasi terhadap Kinerja Pegawai - Surajiyo Surajiyo (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study was to determine the effect of competence and motivation on employee performance. This research uses a quantitative approach with a simple linear regression method. Data collection techniques consist of observation, questionnaire and interview. The results of the study, the Fcount obtained was 10.982> Ftable = 3.25 and the significance level simultaneously significance was 0,000 <(α) = 0.05 df = n - k = 40 -2 - 1 = 37 was 3.25. Conclusions, competence and motivation have a significant effect on the dependent variable, namely performance Keywords: Competence, Motivation, Performance